Effect of copper deficiency upon erythrokinetics in growing cattle. Preliminary results - Marcilese, N. A. (International Atomic Energy Agency; Austria, 1969)
Fil: Marcilese, N. A. Comisión Nacional de Energía Atómica; Argentina